THE ROLE OF GREEN ACCOUNTING AND CAPITAL STRUCTURE ON FINANCIAL PERFORMANCE IN MANUFACTURING COMPANIES - Nurachma Navira; Susi Susilawati (International Journal Management and Economic, 2023)
Financial performance is one of the factors in which a company is able to maintain its survival by developing a thorough plan for all aspects of its business, including financial performance which is a reflection of the company's achievement of success that the company has achieved. The sampling technique used purposive sampling with a total of 50 companies obtained. Data analysis used Eviews 12 software using multiple linear regression analysis. The method used in this research is a quantitative approach and uses secondary data originating from manufacturing company financial reports.This study contributes to green accounting and capital structure which influence manufacturing financial performance. From the results obtained, the variable that really influences financial performance is the capital structure variable, which means that companies with high value tend to produce high ROA, Updates in this research produce a significant influence of capital structure on financial performancer.